The Effect of Work, Family Conflict, and Work Shifts on the Performance of Midwives with Work Stress as Intervening Variables - Achmad, Achmad; Lisdayanti, Lisdayanti; Alim, Andi; Munadhir (Universitas Airlangga, 2023)
Introduction: In hospitals, the most dominant human resources are health workers, especially female midwives who are married and have children. Midwives with these two roles will sometimes experience negative effects, commonly known as work-family conflicts. The purpose of the study was to ascertain the impact of work-family conflict, shift work, and work stress as intervening variables on midwives' performance in Class D General Hospital Pratama Pangkep. Method: The method used is quantitative analysis through a cross-sectional approach. A total of 53 people was the population while a sample of 38 female midwives was taken according to the inclusion criteria. Data collection was carried out using a questionnaire, while data analysis was carried out using path analysis. Result: According to the study's findings, work stress and performance were correlated (p = 0.000), as were work-family conflict and stress at work (p = 0.000), shift work and stress at work (p = 0.000), work-family conflict and performance through work stress (p = 0.004), and shift work and stress at work (p = 0.001). Conclusion: Based on the results of the path analysis conducted, it was found that there is a direct effect between work stress on performance, there is a direct effect between work-family conflict and work shifts on work stress.